Treatment of Hailey-Hailey disease with the Janus kinase inhibitor abrocitinib: A case report - Molly Gunyon; Megha Udupa; Farhan Mahmood; William D. Foulkes; Kevin Pehr; Elena Netchiporouk (SAGE Open Medical Case Reports)
Hailey-Hailey disease is a rare, chronic, autosomal dominant skin disorder characterized by recurrent painful erosions and macerated plaques, primarily affecting intertriginous areas. It is caused by mutations in the ATP2C1 gene, leading to impaired calcium homeostasis and keratinocyte adhesion. Many patients experience poor disease control despite conventional therapies. We report a case of a female in her 60s with refractory Hailey-Hailey disease affecting the perianal, inguinal, and cervical folds, with painful, eroded plaques resistant to conventional treatments. Despite multiple failed therapies, including methotrexate, dapsone, acitretin, and naltrexone, she showed rapid improvement within 2 weeks of abrocitinib (100 mg daily), a JAK1 inhibitor, with sustained control at 2 months follow-up. JAK inhibitors, initially approved for inflammatory diseases such as atopic dermatitis, are emerging as promising therapies for genodermatoses. By suppressing IL-4/IL-13-driven inflammation, JAK1 inhibition may restore epithelial integrity and reduce chronic skin inflammation. This case adds to growing evidence that JAK inhibitors, particularly abrocitinib, may serve as an effective targeted therapy for refractory Hailey-Hailey disease. Further clinical trials are needed to confirm its long-term efficacy and safety.